Different Roles of Microvascular Decompression in Hemifacial Spasm and Trigeminal Neuralgia - Lee, Min Ho; Lee, Jeong-A; Park, Kwan (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objectives Microvascular decompression (MVD) involves the same procedure for both hemifacial spasm (HFS) and trigeminal neuralgia (TN), the resulting clinical courses are different. The aim of this study was to compare differences in MVD operations for HFS and TN and to determine the consequences of these differences on the clinical courses of the two diseases.Methods The medical records of patients who underwent an MVD operation between January 1998 and March 2013 were reviewed.Results A total of 2,263 patients were enrolled, 222 had TN and 2,040 had HFS. In the HFS group, the estimated cure rates at postoperative years 1, 2, and 3 were 92.0, 93.4, and 93.6%. In the TN group, the estimated cure rates at postoperative years 1, 2, and 3 were 88.4, 89.4, and 91.4%. Comparison of the initial treatment response between the HFS and TN groups did not reveal any statistically significant difference (p = 0.338). Among the 1,749 HFS patients initially cured by MVD, 57 were worsened. Among the 181 TN patients treated by MVD, 43 were worsened, with ≥ BNI III (Barrow Neurological Institute pain intensity score III) 12 worsened to a BNI score of IV. Comparing the recurrence rate between the HFS and TN groups, there was a statistically significant difference for cases with ≥ BNI III (p < 0.001), but not in cases with ≥ BNI IV (p = 0.498).Conclusion MVD is a promising treatment for HFS. In contrast, MVD-treated TN had a risk of recurrence. The MVD operation should be carefully considered when applied as a treatment for TN patients.
Keywords: microvascular decompression; hemifacial spasm; trigeminal neuralgia; complication